1999
DOI: 10.1042/bj3430587
|View full text |Cite
|
Sign up to set email alerts
|

The third chitinase gene (chiC) of Serratia marcescens 2170 and the relationship of its product to other bacterial chitinases

Abstract: The third chitinase gene (chiC) of Serratia marcescens 2170, specifying chitinases C1 and C2, was identified. Chitinase C1 lacks a signal sequence and consists of a catalytic domain belonging to glycoside hydrolase family 18, a fibronectin type III-like domain (Fn3 domain) and a C-terminal chitin-binding domain (ChBD). Chitinase C2 corresponds to the catalytic domain of C1 and is probably generated by proteolytic removal of the Fn3 and ChBDs. The loss of the C-terminal portion reduced the hydrolytic activity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 49 publications
2
123
1
4
Order By: Relevance
“…In the S. marcescens chitinases, for example, ChiC exhibits two CBMs connected to the C terminus via a short proteolytically susceptible linker. It is well known that the extra domains add to enzyme efficiency, in particular toward insoluble substrates (67), and it has been shown that this is also the case for ChiC (37). 7 This is often ascribed to proximity effects (68).…”
Section: Discussionmentioning
confidence: 99%
“…In the S. marcescens chitinases, for example, ChiC exhibits two CBMs connected to the C terminus via a short proteolytically susceptible linker. It is well known that the extra domains add to enzyme efficiency, in particular toward insoluble substrates (67), and it has been shown that this is also the case for ChiC (37). 7 This is often ascribed to proximity effects (68).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, removal of only the CBM usually affects activity on insoluble substrates [15,16,[34][35][36][37][38][39][40], while the additional removal of the FNIII domains showed no further effects. In a study of the chitinase A1 from Bacillus circulans WL-12a, the single CBM present was re-attached after removal of one or two intermediate FNIII domains, allowing a direct test for the FNIII function [14].…”
Section: Fniii Domains Function Mainly As Stable Linkersmentioning
confidence: 99%
“…Only in a small number of CBM families (13 out of 66 families), the majority of the CBM members is not located at one of the protein Figure 3. Alignment of all 24 bacterial FNIII domains explicitly reported in literature [2,4,6,15,16,34,36,[38][39][40][41][42][43], in carbohydrate acting enzymes. Sequences were extracted as described in the Methods section, except for the two "FNIII-like domains" from C. thermocellum CbhA (GenBank: CAA56918.1), which were not recognized as such by the domain annotation tools, and were therefore extracted manually [15].…”
Section: Location Of Fniii Domain In the Proteinmentioning
confidence: 99%
“…The catalytic domains of family 18 chitinases have ( / ) 8 -barrel folds and are characterized by several conserved sequence motifs (Terwisscha van Scheltinga et al, 1996;Suzuki et al, 1999). Threedimensional structures have been reported for bacterial family 18 chitinases, such as chitinases A and B from Serratia marcescens and chitinase A1 from Bacillus circulans (Perrakis et al, 1994;van Aalten et al, 2000;Matsumoto et al, 1999).…”
Section: Introductionmentioning
confidence: 99%